Deceleration parameters and their applicability as informal communication signal between pedestrians and automated vehicles. (April 2019) - Ackermann, Claudia; Beggiato, Matthias; Bluhm, Luka-Franziska; Löw, Alexandra; Krems, Josef F.
Highlights: Informal communication for pedestrian-automated vehicle interaction. Perception of deceleration. Recommendations for developers of automated vehicles. Abstract: The proportion of automated vehicles is predicted to steadily increase within the next years. This development is accompanied by several challenges, like the communication between automated vehicles and vulnerable road users, such as pedestrians. The current communication strategies involving the driver, will lose their functionality when interacting with automated vehicles. Due to that, this study focused on vehicle deceleration as informal communication cue. We tested specific parameters (deceleration rate, vehicle speed, onset of deceleration, vehicle size and daylight) within two experimental, video-based simulations in regard to detection performance. Results showed significant shorter reaction times for higher deceleration rate and lower speed. Results for vehicle size and onset of deceleration were mostly influenced by interactions among the parameters. Day light condition did not reveal significance. Within the discussion, we argue to support future communication between automated vehicles and pedestrians by applying smooth and early decelerations, that incorporate vehicle speed as well as vehicle size.